2008
DOI: 10.1002/pola.22585
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion synthesis of nanoparticles containing PEDOT using conducting polymeric surfactant: Synergy for colloid stability and intercalation doping

Abstract: Poly(3,4‐ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) is a widely used conductive aqueous dispersion synthesized by using emulsion polymerization method. To further enhance its solution processability and conductivity of PEDOT derivatives, we proposed to replace the nonconductive PSS with conductive poly[2‐(3thienyl)‐ethoxy‐4‐butylsulfonate] (PTEB) as surfactant for the emulsion polymerization of PEDOT. The reaction involved colloid stabilization and doping in one step, and yielded PEDOT:PTEB co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…. There are two reasons for the increasing electrical conductivity: (1) a surfactant molecule that remains attached to the nPDPA backbone acts as a dopant molecule and electrical conductivity increases, a process known as counter‐ion‐induced doping; (2) the smaller the particle size of nPDPA, the higher the surface area for electron transfer, and thus electrical conductivity is increased . The electrical conductivity of nPDPA is quite different as each surfactant acts as a doping agent.…”
Section: Resultsmentioning
confidence: 99%
“…. There are two reasons for the increasing electrical conductivity: (1) a surfactant molecule that remains attached to the nPDPA backbone acts as a dopant molecule and electrical conductivity increases, a process known as counter‐ion‐induced doping; (2) the smaller the particle size of nPDPA, the higher the surface area for electron transfer, and thus electrical conductivity is increased . The electrical conductivity of nPDPA is quite different as each surfactant acts as a doping agent.…”
Section: Resultsmentioning
confidence: 99%
“…1b, the FT-IR of pristine PEDOT, PEDOT/CNTs (50 wt.% PEDOT) and PEDOT/PSS-CNTs (50 wt.% PEDOT) nanocomposite all show the characteristic peaks of pristine PEDOT. Notably, the vibrations at around 1336-1519 cm −1 are attribute to C-C and C C stretching of quinoidal structure and ring stretching of thiophene ring (similar to benzoidal structure) [32]. Further vibrations at about 1150 and 1000 cm −1 are both assigned to the stretching modes of the C-O-C bond, and the peak at 920 cm −1 is corresponding to the ethylenedioxy group in the molecule deformation mode [33].…”
Section: Structural Characterization and Morphology Analysismentioning
confidence: 97%
“…A gradual peak at 2θ ≈ 23.6° clearly appears in the XRD pattern, and it is assigned to the (0 2 0) reflection. The XRD pattern for PEDOT nanoparticles in general shows three peaks: 6.1–6.7° for the (1 0 0) reflection, 12.1–12.8° for the (2 0 0) reflections and 25.0–25.8° for the (0 2 0) reflection,8, 12, 13, 26 while there is a report that a single major peak assigned to the (0 2 0) reflection solely appears24 and it is in agreement with our observation. The (0 2 0) reflection peak shift to a lower angle (i.e., 25° to 23.6°) shows that the packing of the PEDOT backbone planes is loose due to insufficient p ‐doping, and thus the face‐to‐face distance between the stacked p ‐doped PEDOT sheets becomes long.…”
Section: Resultsmentioning
confidence: 99%
“…Most of research reports on the preparation of PEDOT nanoparticles have not evidently shown separate particles with clear structures and definite morphologies. The electron microscopy images of PEDOT nanoparticles published to date8, 9, 11–14, 16, 21–25, 29 show an inclination toward the aggregation of particles. The formation of irregular aggregated structures is known to be induced by π‐π stacking interactions between PEDOT nanoparticles 25.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation